The ARSQ: The Athletes` Received Support Questionnaire - Freeman, P.; Coffee, P.; Moll, T.; Rees, T.; Sammy, N. (Journal of Sport & Exercise Psychology, 2014)
To address calls for context-specific measurement of social support, this article reports the development of the Athletes` Received Support Questionnaire (ARSQ) and demonstrates initial evidence for its validity. Across four studies there was support for a four-dimensional structure reflecting emotional, esteem, informational, and tangible received support. There was also support for unidimensional and higher-order models. Further, Study 3 provided some support for convergent validity, with significant correlations between the corresponding dimensions of the ARSQ and the Inventory of Socially Supportive Behaviors. Study 4 provided evidence for the nomological validity of the ARSQ. Emotional and esteem support significantly predicted self-confidence and positive affect, and tangible support significantly moderated the relationship between stress and negative affect. Collectively, these results provide initial evidence for the validity of the ARSQ, and offer researchers flexibility to adopt either a multidimensional or aggregated approach to measuring received support.